Teachers' Perceptions and Challenges in Using Blended Learning for Teaching English in the New Normal Era - Khairunnisa, Salsabila (RETAIN : Journal of Research in English Language Teaching, 2022)
This research concerns EFL teachers’perceptionsand challenges in using blended learning to teach English in the New Normal Era. Therefore,identifyingtheirperceptions of using blended learning and its challenges becomes the objective of this research. Aqualitativestudy was conducted by involving two junior high school English teachers in Surabaya. It wasfound that teachers' perceptions of the use of blended learning are very positive. The teachers supported the use of blended learning since it has advantages in the learning process. Students can learn at the same time in online and offline lessons. They are also more enthusiastic about learning in mixed learning techniquebecause it is easier for them to access materials on the online platform. However, there are still some challenges that the teacher mentioned, such as poor internet network, low student motivation,the preparation for using blended learningand the problem of electricity.